2016
DOI: 10.1007/s40415-016-0320-9
|View full text |Cite
|
Sign up to set email alerts
|

Is the application of arbuscular mycorrhizal fungi an alternative to increase foliar phenolic compounds in seedlings of Mimosa tenuiflora (Wild.) Poir., Mimosoideae?

Abstract: The legume Mimosa tenuiflora (Wild) Poir occurs in the ''Caatinga'' and is used as a popular remedy because of its medicinal properties related to the presence of secondary compounds in several parts of the plant. The arbuscular mycorrhizal fungi (AMF) are associated with most legumes, including M. tenuiflora, benefiting the growing process and the production of secondary compounds; however, the production of phytochemicals in response to AMF inoculation has not been defined yet. The aim of this study was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In contrast, the production of phenols and total proanthocyanidins in the leaves of yellow passionfruit associated with A. longula did not differ from the control without inoculation. When working with Mimosa tenuiflora , Silva and Silva reported that the inoculation with AMF did not enhance the production of any biomolecule in the leaf assessed.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the production of phenols and total proanthocyanidins in the leaves of yellow passionfruit associated with A. longula did not differ from the control without inoculation. When working with Mimosa tenuiflora , Silva and Silva reported that the inoculation with AMF did not enhance the production of any biomolecule in the leaf assessed.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that phenolic compounds may grant pharmacological properties 37 . In contrast, divergent results were found by Silva and Silva, 38 since the mycorrhization did not favor the production of biomolecules in Mimosa tenuiflora (Willd.) Poiret.…”
Section: Discussionmentioning
confidence: 89%
“…Mycorrhizal H. perforatum had lower flower numbers and stem diameter than non-inoculated plants (Lazzara et al, 2017). Silva and Silva (2017) also documented that mycorrhization did not benefit primary and secondary metabolism production and the growth of Mimosa tenuiflora (Wild)…”
Section: Amf and Production Of Metabolitesmentioning
confidence: 92%